2014
DOI: 10.3325/cmj.2014.55.638
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in inflammatory response genes and their associations with breast cancer risk

Abstract: AimTo explore the association of NFKB1 c.-798_-795delATTG (rs28362491), NFKBIA c.-949C>T (rs2233406), IL-8 c.-352A>T (rs4073), IL-10 c.-854T>C (rs1800871), TNF c.-418G>A (rs361525), and TNF c.-488G>A (rs1800629) polymorphisms with breast cancer risk in an East Chinese population.MethodsWe conducted a case-control study including 975 study participants (474 breast cancer patients and 501 female controls without cancer) and genotyped the polymorphisms employing polymerase chain reaction-restriction fragment leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“… 38 In addition, previous studies have confirmed that A allele is associated with an increased risk of many cancer types. 19 , 20 , 39 Recently, several meta-analysis have been conducted and have identified that rs4073 polymorphism was related to an increased risk of overall cancers and potentially offered an evidence-based medical certificate to investigate cancer risk. 35 , 40 , 41 Considering that a large number of meta-analyses concentrated on IL-8 rs4073 polymorphism and cancer risk were performed, we focus only on several other polymorphisms in IL-8 and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 38 In addition, previous studies have confirmed that A allele is associated with an increased risk of many cancer types. 19 , 20 , 39 Recently, several meta-analysis have been conducted and have identified that rs4073 polymorphism was related to an increased risk of overall cancers and potentially offered an evidence-based medical certificate to investigate cancer risk. 35 , 40 , 41 Considering that a large number of meta-analyses concentrated on IL-8 rs4073 polymorphism and cancer risk were performed, we focus only on several other polymorphisms in IL-8 and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 19 identified that no association of rs4073, rs2227306, −353A/T, and +678T/C polymorphisms in IL-8 gene and HCC risk was revealed in the Chinese population. Then, Wang et al 39 performed a case–control study enrolling 474 breast cancer patients and 501 female nontumor controls and identified that TT genotype of IL-8 rs4073 polymorphism has a significantly reduced risk of breast cancer (TT: OR =0.48, 95% CI =0.33–0.72, P <0.001). In another study, Liu et al 20 enrolled 270 patients with oral squamous cell carcinoma and 350 healthy controls, and their results demonstrated that four polymorphisms (rs4073, rs2227306, +1633C/T, and +276A/T) were not related to the risk of oral cancer or clinic pathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence suggesting a relationship between TNF − 308, IL-6 rs1800795, and sepsis risk, other researchers could not find a consistent association between the SNPs and the risks of sepsis and outcomes [14]. Moreover, many previous studies reported a higher prevalence of IL-6 rs1800795 and rs1800629 polymorphisms and a connection with a variety of diseases in the Chinese Han population [15][16][17][18].…”
Section: Introductionmentioning
confidence: 91%
“…Polymorphisms of the IL-8 gene have been implicated in several human diseases. For instance, the +781C/T and −352A/T polymorphisms of IL-8 gene are related to cancer development, [10,11] while the 4073A/T polymorphism is associated with myocardial infarction. [12] Interestingly, increasing evidence has suggested that polymorphisms of inflammation-related genes may be associated with PE development, such as tumor necrosis factor-α, IL-10, and IL1A.…”
Section: Introductionmentioning
confidence: 99%